GAMBARAN PELAKSANAAN POSYANDU REMAJA DI KELURAHAN PANGGUNG KIDUL KECAMATAN SEMARANG UTARA - Laila Wahid; Ratih Indraswari; Zahroh Shaluhiyah; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Adolescent integrated health service (posyandu remaja) the one of goverment programs for teenagers in understanding health issues, finding alternative problem solving, forming support group, expanding the reach PKPR. The formation adolescent integrated health service Panggung Kidul of North Semarang sub-district is a guideline of adolescent integrated health service in Semarang after being inaugurated in January 2019. This research aims to analyze the implementation of adolescent integrated health service Panggung Kidul North Semarang sub-district with a system theory approach. This research uses qualitative methods. The research subject amounted to 12 people, consist of 5 cadres, 2 youth participants, 2 families, 1 public health care officer, 1 community figure and 1 person in the village health forum (FKK) taken by using purposive sampling and data collection techniques through indepth interviews. The results showed that problems including inadequate human resources, training about cadres, sources of fund is unclear, infrastructure facilities and guidelines are less complete. The implementation of adolescent integrated health service also need innovations with interesting presentations so that participants are not bored. Evaluation is still not implemented and support of Puskesmas, family, and community leaders also FKK is still indispensable and communication need to be improved for the implementation of adolescent integrated health service.